Laboratory and Self-Report Methods to Assess Reappraisal and Distraction in Youth. Issue 6 (2nd November 2019) - Bettis, Alexandra H.; Henry, Lauren; Prussien, Kemar V.; Vreeland, Allison; Smith, Michele; Adery, Laura H.; Compas, Bruce E.
Abstract : Coping and emotion regulation are central features of risk and resilience in childhood and adolescence, but research on these constructs has relied on different methods of assessment. The current study aimed to bridge the gap between questionnaire and experimental methods of measuring secondary control coping strategies, specifically distraction and cognitive reappraisal, and examine associations with symptoms of anxiety and depression in youth. A community sample of 70 youth (ages 9–15) completed a novel experimental coping and emotion regulation paradigm and self-report measures of coping and emotion regulation and symptoms. Findings indicate that use of distraction and reappraisal during the laboratory paradigm was associated with lower levels of negative emotion during the task. Youth emotion ratings while implementing distraction, but not reappraisal, during the laboratory task were associated with youth self-reported use of secondary control coping in response to family stress. Youth symptoms of anxiety and depression were also significantly positively associated with negative emotion ratings during the laboratory task, and both laboratory task and self-reported coping and emotion regulation accounted for significant variance in symptoms in youth. Both questionnaire and laboratory methods to assess coping and emotion regulation in youth are important for understanding these processes as possible mechanisms of risk and resilience and continued integration of these methods is a priority for future research.